2011
DOI: 10.1128/aem.05111-11
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Plasticity of the Intracellular Plant Pathogen and Insect Symbiont “Candidatus Liberibacter asiaticus” as Revealed by Hypervariable Prophage Genes with Intragenic Tandem Repeats

Abstract: "Candidatus Liberibacter asiaticus" is a psyllid-transmitted, phloem-limited alphaproteobacterium and the most prevalent species of "Ca. Liberibacter" associated with a devastating worldwide citrus disease known as huanglongbing (HLB). Two related and hypervariable genes (hyv I and hyv II ) were identified in the prophage regions of the Psy62 "Ca. Liberibacter asiaticus" genome. Sequence analyses of the hyv I and hyv II genes in 35 "Ca. Liberibacter asiaticus" DNA isolates collected globally revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 48 publications
(46 reference statements)
2
61
1
Order By: Relevance
“…Quantification of bacterial titers used a series of primer LJ900fr, forward primer (5-GCCGTTTTAACACAAAAGATGAATATC-3), and reverse primer (5-ATAAATCAATTTGTTCTAGTTTACGAC-3) (Zhou et al, 2011). Real-time PCR reaction mix used 20 µl contained 10 µl of universal real-time mix with SYBR green (Kappa), 1 µl of each primer, 1 µl of DNA sample (50 ng/µl), and 7 µl H 2 O.…”
Section: Candidatus Liberibacter Asiaticus (Clas) Titers By Real-timementioning
confidence: 99%
“…Quantification of bacterial titers used a series of primer LJ900fr, forward primer (5-GCCGTTTTAACACAAAAGATGAATATC-3), and reverse primer (5-ATAAATCAATTTGTTCTAGTTTACGAC-3) (Zhou et al, 2011). Real-time PCR reaction mix used 20 µl contained 10 µl of universal real-time mix with SYBR green (Kappa), 1 µl of each primer, 1 µl of DNA sample (50 ng/µl), and 7 µl H 2 O.…”
Section: Candidatus Liberibacter Asiaticus (Clas) Titers By Real-timementioning
confidence: 99%
“…No transposon was annotated in the complete sequences of three phages/prophages of "Ca. Liberibacter asiaticus," SC1, SC2, and FP2 (23,24). In sequence analyses, two characteristics are highly indicative of transposons: presence of TIRs and identification of a transposase gene (tps).…”
mentioning
confidence: 99%
“…In the past few years, there have been several reports of DNA polymorphisms in "Ca. Liberibacter asiaticus" populations using single primer sets (24,(26)(27)(28)(29). By analyzing two Chinese "Ca.…”
mentioning
confidence: 99%
“…The lasA I and lasA II , previously reported as hyv I and hy v II , are located in two prophage regions in the Las Psy62 genome [17]. The 2760 bp lasA I encodes a 919 amino-acid hypothetical protein with a predicted molecular mass of 103.5 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…Within these prophage regions, two hypothetical hypervariable proteins (Hyv I and Hyv II ) were identified that contained multiple, nearly-identical, leucine-rich repeats (LRRs). The diversity and plasticity of these two genes may have implications for how these intracellular bacteria adapt to their host ecological niches [17]. …”
Section: Introductionmentioning
confidence: 99%